Management of Overtourism Problems in Small Historical Towns. Case of Suzdal, Russia - ALEXANDROVA, Anna Yu.; AIGINA, Ekaterina V.; KAVERZIN, Igor L.; SHERESHEVA, Marina Yu. (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019, 2020)
Active tourism development in Suzdal – world-famous town-museum and UNESCO Heritage site in Vladimir region, Russia – forms the growing pressure on its heritage and the local community. The tourist flows, extremely uneven both in time and space, cause overcrowding and substantial discontent of the local residents. The research discusses the ways of managing overtourism problems through the long-term engagement with the local community using diversified event calendar, specially tailored tourist products, new tourist zones, transport and information infrastructure development as well as additional measures to support the local budget.